PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS LEMBAR HASIL OBSERVASI PADA SISWA KELAS X.2 SMA SARASWATI 1 DENPASAR TAHUN PELAJARAN 2024/2025 - Sanul, Yolastika; Sukanadi, Ni Luh; Putra, I Komang Widana (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2025)
his study is a classroom action research (PTK) which aims to (1) Determine theapplication of the PBL (Problem Based Learning) learning model to improve thewriting skills of observation sheet texts for class X.2 students of SMA Saraswati 1Denpasar in the 2024/2025 Academic Year (2) determine the steps for implementingthe problem based learning model to improve the writing skills of observation sheettexts for class X.2 students of SMA Saraswati 1 Denpasar in the 2024/2025 AcademicYear. Data collection using observation and tests. The data obtained were thenanalyzed descriptively qualitatively and quantitatively. The results of the study showedthat the application of the PBL (Problem Based Learning) model to improve the writingskills of observation sheet texts for class X.2 students of SMA Saraswati 1 Denpasar.The increase in student activity can be seen from the enthusiasm of students inresponding to learning. Students are active in learning in class and are able tounderstand the material and complete the tasks given. Furthermore, when viewed fromthe results of student learning, the improvement of the results of writing the text of theobservation sheet results can be seen from the assignments given by educators tostudents and can be reviewed from the average score of the students’ tests. In the pre-test stage, students obtained an average score of 52.58 in cycle 1 56.58 and in cycle IIstudents obtained an average score of 80.67. can improve students’ability in writingLHO texts. This is shown by the results of each cycle seen from students who are ableto can be seen from students who are able to arrange the appropriateness of the content, the accuracy of the use of language, the appropriateness of the writing on students about the text of the observation sheet results. Abstrak Penelitian ini merupakan penelitian tindakan kelas (PTK) yang bertujuan (1) mengetahui penerapan model pembelajaran PBL (Problem based learning) untuk meningkatkan keterampilan menulis teks lembar hasil observasi pada siswa kelas X.2SMA Saraswati 1 Denpasar Tahun Pelajaran 2024/2025, (2) mengetahui langkah-langkah penerapan model pembelajaran problem based learning untuk meningkatkan keterampilan menulis teks lembar hasil observasi pada siswa kelas X.2 SMA Saraswati 1 Denpasar Tahun Pelajaran 2024/2025. Pengumpulan data mengunakan observasi dan tes. Data yang diperoleh kemudian dianalisis secara deskriptif kualitatif dan kuantitatif. Hasil penelitian menunjukan bahwa penerapan model PBL(pembelajaran Problem based learning) untuk meningkatkan keterampilan menulis teks lembar hasil observasi pada siswa kelas X.2 SMA Saraswati 1 Denpasar. Meningkatnya aktivitas siswa tampak dari keantusiasan siswa dalam merespon pembelajaran. Siswa aktif dalam pembelajaran di kelas dan mampu memahami materi serta meyelesaikan tiga yang diberikan. Selanjutnya, jika ditinjau dari hasil belajar siswa, peningkatan hasil menulis teks lembar hasil observasi terlihat dari penugasan yang diberikan oleh pendidik kepada siswa dan dapat ditinjau dari nilai rata-rata tessiswa. Pada tahap pre-tes siswa memperoleh nilai rata-rata 36,12 pada siklus I 46,16dan pada siklus II siswa memperoleh nilai rata-rata 80,67. Dapat meningkatkan kemampuan siswa dalam menulis teks laporan hasil observasi.Hal itu ditunjukan oleh hasil setiap siklus Hal tersebut dapat terlihat dari siswa yang mampu merangkai kesesuaian isi, ketepatan pengunaan bahasa, kesesuaian tulisan pada siswa tentang teks lembar hasil observasi.